Application of positively-charged ethylenediamine-functionalized graphene for the sorption of anionic organic contaminants from water. Issue 3 (September 2016) - Cai, Nan; Larese-Casanova, Philip
Graphical abstract: Highlights: Graphene oxide was functionalized with ethylenediamine molecules. Positive surface charge on functionalized graphene promoted organic anion sorption. Sorption extent is strongly influenced by solution pH. Electrostatic interactions likely govern sorption of charged molecules. Abstract: Graphene materials represent a new carbonaceous sorbent for the removal of organic micropollutants from water, and most applications of graphene utilize an oxidized, negatively-charged surface to improve dispersibility. However, classes of anionic micropollutants may undergo less sorption than cationic or neutral compounds on graphene oxide due to electrostatic repulsion forces. This work seeks to improve the sorptive capability of graphene for anionic micropollutants through amending surfaces with positive charges. Graphene oxide was functionalized with ethylenediamine (ED-G) through an acyl chlorination and amidation process that allows a net positive surface charge at pH < 8.1. ED-G held greater sorption capacity for anionic ibuprofen compared to cationic atenolol and neutral carbamazepine for nearly all water conditions within batch reactors. Ibuprofen sorption greatly increased, and atenolol sorption decreased, at more acidic solution pH. Competitive sorption experiments showed that ibuprofen is consistently preferred on ED-G over atenolol over a wide range of concentrations, and the presence of other anionic compounds can suppress the sorption of ibuprofen. These trends in sorption extent, sorbate charge, and sorbent charge indicate electrostatic interactions largely govern the binding of sorbate molecules. Consequently, a positively-charged graphene material could enhance the removal of anionic micropollutants within water treatment systems compared to graphene oxide.